Method for analyzing infiltration degree of battery cell
By conducting multi-dimensional regional testing on the lithium-ion battery electrodes, quantitative analysis of characteristic elements contents was solved, and the problem of uneven infiltration of electrolyte was achieved and the battery performance and safety was improved.
Patent Information
- Application Number
- CN202411404789.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The prior art is difficult to accurately evaluate the infiltration of lithium-ion battery electrolyte in the electrode sheet, resulting in uneven current density distribution, degraded battery performance and safety hazards.
By conducting regional testing of the electrode sheet from multiple dimensions, quantitatively analyzing the content of characteristic elements, determining the degree of infiltration of the electrode sheet, and then targeting electrolyte distribution control and performance improvement.
Accurate quantitative analysis of the distribution of electrolyte in the electrode sheet is achieved, the circulation and safety performance of the battery is improved, and lithium excretion phenomenon and battery life are shortened.
Smart Images

Figure CN119394850A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for analyzing the degree of wetting of a battery cell. Background Art
[0002] Currently, lithium-ion batteries have been widely developed in 3C electronic devices, electric vehicles and energy storage fields, and the market demand for lithium-ion batteries with higher energy density and better performance has increased dramatically. In the development of high-energy-density lithium-ion batteries, the key technical challenges faced are how to improve the capacity utilization of electrodes and improve the difficulty of wetting caused by high compaction density. Effectively improving the wettability of the electrolyte is considered to be the key to solving this problem. In the manufacture of lithium-ion batteries, uneven wetting will lead to uneven current density distribution and unstable electrolyte interface film (SEI); at the same time, incomplete wetting directly affects the performance of the battery, leading to the occurrence of lithium precipitation and causing a series of safety issues. In short, the raw material electrolyte of lithium-ion batteries is the core part of lithium-ion battery research and development, and the consideration and evaluation of the wettability of the electrolyte to the electrode is the key to the development of high-performance lithium-ion batteries.
[0003] At present, the infiltration detection technology is very limited, such as: calculating the dry area method, EDS testing the P element content method, and observing the full-charge interface method. The calculation of the dry area method and the observation of the full-charge interface method are both visual level methods. The calculation of the dry area method can only detect the infiltration situation macroscopically; the observation of the full-charge interface method can be used to determine whether the infiltration is sufficient by observing whether there are dark spots on the full-charge interface after formation. Because the formation of the full-charge interface is related to many factors, such as film formation, the wavy edge of the electrode, etc., this method has great limitations. The EDS test P element content method uses EDS to measure the difference in P element content in each area of the electrode to obtain the difference in infiltration, which can be used to characterize the infiltration. It mainly uses electron microscope surface scanning analysis to determine the distribution position of the P element in the material, and then determines the P element content at the specific position by point scanning. The test accuracy is low, usually only a few selected areas can be scanned, and often only the P element content of the surface is tested. Therefore, this method is not accurate at the microscopic level, so it is also a semi-quantitative detection method. In addition, since insufficient wetting will eventually affect the cycle performance, whether the wetting is sufficient can be judged based on whether the cycle performance meets the specification requirements and the capacity retention rate. However, since there are too many factors affecting the cycle performance, this method cannot effectively characterize the wettability.
[0004] Therefore, the above-mentioned existing methods generally have the disadvantages of poor repeatability and inability to accurately evaluate the actual wetting conditions of the electrolyte. It is necessary to develop a more accurate analysis method for the electrolyte wetting properties, realize quantitative detection of the electrolyte distribution, and then carry out targeted control and performance improvement. Summary of the invention
[0005] In order to solve the problems and shortcomings existing in the prior art, the present invention provides a method for analyzing the wetting degree of a battery cell, which can quantitatively analyze the distribution of the electrolyte in the electrode, and thus can carry out targeted electrolyte distribution control and performance improvement, thereby effectively optimizing the electrochemical properties such as the cycle performance of the battery.
[0006] The present invention provides a method for analyzing the degree of wetting of a battery cell, comprising the following steps: S1. disassembling a battery cell in an empty state after being transformed to obtain a pole piece; the pole piece contains an electrolyte, and the electrolyte contains characteristic elements; the pole piece includes at least one of a positive pole piece and a negative pole piece; S2. dividing the pole piece into n regions in the length direction, and further dividing the pole piece into m regions in the width direction at the center position in the length direction of each region, to obtain K first sample regions to be tested, K=n×m; the length of the first sample region to be tested is L1, the width is W1, and the thickness is H1; at the same time, using the current collector as a dividing line, the pole piece is divided into a front side and a back side, and the front side and the back side are divided into x regions in the width direction in turn, and each region is divided into y regions in the thickness direction, to obtain Y second sample regions to be tested, Y=2×x×y; the length of the second sample region to be tested is L2, the width is W2, and the thickness is H2; S3 . Test the content of characteristic elements in K first test sample areas and Y second test sample areas in the electrode; the characteristic elements include at least one of P, S, B, F, N, Si, Al, As, Bi, Ca, Cd, Co, Cr, Cu, Fe, Ga, Ge, In, Ir, K, La, Li, Mg, Mn, Mo, Na, Nb, Ni, Pb, Sb, Sn, Sr, Ta, Ti, V, W, Y, Zn, and Zr; S4. When the ratio of the characteristic element content of any two areas in the first test sample area of the electrode is greater than 2, the characteristic element content of the area with lower characteristic element content is used as the divisor; and / or, when the ratio of the characteristic element content of any two areas in the second test sample area of the electrode is greater than 2, the characteristic element content of the area with lower characteristic element content is used as the divisor; judge that the degree of wetting of the electrode is insufficient.
[0007] In some cases, during the operation of the battery cell, the electrolyte may remain in certain locations inside the battery cell and fail to fully penetrate between the positive and negative electrodes and the edge of the battery cell, resulting in electrolyte dripping in some areas. This is insufficient electrolyte infiltration. When the electrolyte is insufficiently infiltrated, the following problems will occur: (1) Lithium deposition occurs inside or at the edge of the battery cell. In the case of insufficient electrolyte infiltration, the positive and negative electrodes of lithium ions can easily meet inside the battery cell, causing heat release and gas release, thereby squeezing out the electrolyte and forming lithium deposition. Once lithium deposition is serious, it will not only affect the performance and life of the battery cell, but also cause safety hazards. (2) Shortened battery cell life. The electrolyte is one of the important components of the battery cell. If the electrolyte is insufficiently infiltrated, it will seriously affect the service life of the battery cell.
[0008] Therefore, how to accurately evaluate the wetting of the electrolyte in the battery cell to the electrode plays a key role in further effectively improving the performance and life of the battery cell.
[0009] The electrolyte is composed of solvents, additives, and lithium salts. Generally speaking, the relative molecular mass of the solvent is small (for example, EC: 88.06, DMC: 90.08, generally within 100), and the content is high, so it is easier to infiltrate. The relative molecular mass of lithium salts and additives is high, and the content is low, so it is difficult to infiltrate, especially additives. Some functional additives are added to the electrolyte in a small proportion (0.5-2%), and have a significant effect on the performance of the battery cell. Therefore, we pay more attention to the distribution of additives or some difficult-to-infiltrate lithium salts in the pole piece. Analyzing the electrolyte composition from the elemental composition, C, H, and O elements are commonly contained in each component. In addition to C, H, and O, there are other elements that can distinguish the components of the electrolyte, which are called characteristic elements. For example, lithium salt is usually LiPF6, and P and F are the characteristic elements of this component. Additives usually include PS, LIFSI, LiODFB, etc. PS contains the characteristic element S, LIFSI contains the characteristic elements S, F, and N, and LiODFB contains the characteristic elements F and B. Therefore, for additives or some lithium salts, we can analyze the distribution of the electrolyte in the battery cell by analyzing the distribution of the characteristic elements they contain in the battery cell (mainly the positive and negative electrodes, and of course the separator), and then improve the areas where the electrolyte infiltration is insufficient, and further optimize the cycle performance and safety performance of the battery cell. Moreover, because the additives and some lithium salts are more difficult to infiltrate in the electrolyte components, and these components have a greater impact on the performance of the battery, analyzing the distribution of the characteristic elements contained in the additives and these lithium salts in the battery cell can more accurately indicate the distribution of the additives and these lithium salts in the battery cell, that is, it is more accurate to analyze the degree of electrolyte infiltration into the battery cell, and thus can more clearly define the direction to optimize the electrolyte infiltration performance and improve the electrochemical performance of the battery.
[0010] Therefore, the present invention mainly tests the content of relevant characteristic elements in multiple regions of the pole piece in the general direction based on the length and thickness dimensions of the pole piece, that is, by dividing the pole piece from multiple dimensions and analyzing the content of characteristic elements in these regions, the characteristic element content of all regions of the pole piece can be basically covered, so that a more accurate quantitative analysis of the degree of electrolyte infiltration on the pole piece can be made. Furthermore, by comparing and analyzing the characteristic element content of these regions, it is possible to analyze which regions of the pole piece have insufficient infiltration, and take targeted measures to improve the infiltration degree of these regions, thereby improving the overall infiltration degree of the pole piece and achieving the purpose of optimizing battery performance.
[0011] It should also be noted that the method for analyzing the degree of wetting of battery cells provided by the present invention is a quantitative analysis of the content of characteristic elements in multiple areas of the electrode. Therefore, compared with the methods of the prior art, it is a relatively accurate and effective method for characterizing the degree of wetting of battery cells. Therefore, it has important practical significance for guiding the further optimization of the wetting performance of battery cells to further optimize the battery performance.
[0012] Preferably, in S2, in the K first sample areas to be tested, when the electrode is a positive electrode, L1≥50mm, W1≥19.6mm, H1≥106μm; when the electrode is a negative electrode, L1≥50mm, W1≥19.6mm, H1≥130μm; in the Y second sample areas to be tested, when the electrode is a positive electrode, L2≥1492mm, W2≥19.1mm, H2≥17.6μm; when the electrode is a negative electrode, L2≥1563mm, W2≥19.6mm, H2≥21.6μm. When dividing the regions in terms of the length and thickness of the electrode, the present invention controls the size of each sample area to be tested within a certain range, so that when the powder is scraped from the electrode to test the content of characteristic elements, there is enough sample volume to carry out relevant tests, avoiding inaccurate test results due to too little sample volume, which affects the accurate analysis of the degree of wetting of the electrode and the battery cell.
[0013] Preferably, in S2, when the pole piece is a positive pole piece, L1=50mm, W1=19.6mm, H1=106μm; when the pole piece is a negative pole piece, L1=50mm, W1=19.6mm, H1=130μm; when the pole piece is a positive pole piece, L2=1492mm, W2=19.1mm, H2=17.6μm; when the pole piece is a negative pole piece, L2=1563mm, W2=19.6mm, H2=21.6μm. When the areas are divided for sampling in the length and thickness directions respectively, and the size of the sample area to be tested is the above-mentioned value, when the powder is scraped from the electrode to test the content of characteristic elements, it can ensure that there is enough sample quantity for relevant tests to avoid inaccurate test results due to too little sample quantity, which affects the accurate analysis of the wetting degree of the electrode and the battery cell; it can also ensure that the electrode can be divided into relatively sufficient areas to ensure that all areas of the electrode are fully covered, improve the accuracy of the analysis results of the electrolyte wetting degree, and more accurately improve the wetting performance of the electrode area with insufficient wetting, thereby optimizing battery performance.
[0014] Preferably, in S2, K≥9; Y≥18. It is ensured that when the electrode is divided into regions by length and thickness, more divided regions are obtained, which can more accurately characterize the electrolyte infiltration of each region of the electrode, thereby more accurately characterizing the infiltration degree of the electrode and the battery cell as a whole, and can provide a more accurate improvement direction on how to further improve the infiltration degree of the electrode and the battery cell.
[0015] Preferably, in S2, K=9; Y=18.
[0016] Preferably, in S2, the characteristic elements include at least one of P, S, and B.
[0017] Preferably, in S2, the characteristic element content in the pole piece is tested using an inductively coupled plasma spectrometer. Inductively coupled plasma spectrometer test is referred to as ICP test. The ICP test method is used to test the characteristic element content in the pole piece, which has high accuracy, especially for the ppm content level. It can also achieve relatively accurate testing, so it can more accurately characterize the infiltration situation in the battery cell.
[0018] Preferably, the electrolyte includes the following components: lithium salt, organic solvent, film-forming additive, functional additive; the mass ratio of lithium salt: organic solvent: film-forming additive: functional additive is 12-18:74-85:2-5:1-4; the lithium salt includes lithium hexafluorophosphate; the organic solvent includes at least one of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; the film-forming additive includes at least one of fluoroethylene carbonate and vinylene carbonate; the functional additive includes at least one of lithium bis(fluorosulfonyl)imide, lithium difluorobis(oxalatophosphate), lithium difluorophosphate, lithium bis(oxalatoborate), 1,3-propanesultone, and vinyl sulfate. The method for analyzing the wetting degree of a battery cell provided by the present invention is applicable to a variety of electrolyte components, and in particular, for the electrolyte with the above-mentioned ratio and material composition, the method provided by the present invention has greater adaptability to analyzing its wetting degree on the battery cell, and can have a more accurate analysis of the additives therein and the characteristic element content in the lithium salt, that is, it can more accurately analyze the wetting degree of the electrolyte in the battery cell, and can more accurately optimize the wetting performance of the battery cell.
[0019] Preferably, the positive electrode sheet includes a positive electrode material, a first conductive agent, and a first binder; the mass ratio of the positive electrode material, the first conductive agent, and the first binder is 95-99: 1-3.5: 0.5-1.5; the positive electrode material includes at least one of lithium iron phosphate positive electrode material, ternary nickel cobalt lithium manganese oxide positive electrode material, and lithium iron manganese phosphate positive electrode material; the first conductive agent includes at least one of conductive carbon black and carbon nanotubes; the first binder includes at least one of polyvinylidene fluoride; the negative electrode sheet includes a negative electrode material, a second conductive agent, and a second binder; the mass ratio of the negative electrode material, the second conductive agent, and the second binder is 95-99: 0.3-2: 1-3.5; the negative electrode material includes at least one of natural graphite, artificial graphite, and silicon-carbon negative electrode; the second conductive agent includes conductive carbon black; the second binder includes at least one of carboxymethyl cellulose and styrene-butadiene rubber. For the above-mentioned compositions of positive and negative electrodes that are more commonly used in the market, the analysis method provided by the present invention has greater adaptability, and therefore has important guiding significance for analyzing current lithium batteries on how to further improve the wetting performance of battery cells to improve battery performance.
[0020] Preferably, the battery cell comprises a cylindrical battery cell. In the cylindrical battery cell, when the battery cell is injected, after the electrolyte enters the bottom of the shell from the center hole of the core, the electrolyte gradually flows and penetrates from the positive and negative ends to the middle position. The electrolyte is composed of lithium salts, solvents and additives. Different components have different molecular weights and molecular diameters; there are also differences in distribution equilibrium properties. According to the column chromatography model: the core can be regarded as the stationary phase, and the electrolyte is the mobile phase. When the two phases move relative to each other, due to the differences in the distribution equilibrium properties of the components in the electrolyte, the concentrations of the components of the electrolyte in the stationary phase are different. In addition, the pores in the pole piece or diaphragm have a certain filtering effect on the electrolyte. The above factors cause the distribution or infiltration degree of the electrolyte in various places in the cylindrical battery cell to be different, resulting in a decrease in the performance of the cylindrical battery cell. Therefore, the analysis of the degree of electrolyte infiltration in the cylindrical battery cell is of greater significance in the field of lithium batteries. The method provided by the present invention can relatively accurately analyze the degree of electrolyte infiltration in the cylindrical battery cell, and therefore has more important guiding significance for further optimizing the overall infiltration degree of the cylindrical battery cell and improving the performance of the cylindrical battery cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 1C / 3C room temperature cycle performance of the A / B / C battery cells in Example 1.
[0022] Figure 2 This is a sampling schematic diagram of dividing the pole piece into regions along the length direction in Example 1 (dividing the regions along the length direction first and then along the width direction).
[0023] Figure 3This is a sampling schematic diagram of dividing the electrode into regions in the thickness direction in Example 1 (dividing the regions in the width direction first and then in the thickness direction).
[0024] Figure 4 The 1C / 5C room temperature cycle performance of the improved A / B battery cells in Example 1 and the original C battery cell (control group). DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.
[0026] Example 1
[0027] According to the process of homogenization-coating-rolling-slitting-winding-assembly-forming, three batches of cylindrical cells were made in the laboratory, namely A / B / C. The positive electrode sheet formula is ternary nickel cobalt manganese oxide: 97%, SP: 1.2%, CNT: 0.8%, PVDF: 1%; the negative electrode sheet formula is graphite: 97%, SP: 0.8%, CMC: 1%, SBR: 1.2%. The dimensions of the positive and negative electrode sheets in the battery cell are shown in Table 1.
[0028] Table 1 Dimensions of positive and negative electrodes of the battery cell
[0029]
[0030] And the electrolyte formula in this embodiment is, EC (ethylene carbonate): 15.60%, DMC (dimethyl carbonate): 55.35%, EMC (ethyl methyl carbonate): 7.45%, LiPF6: 16%, LiFSI: 0.8%, FEC: 3.0%, LiODFB: 0.8%, PS: 1%. The formula of the battery cells is the same, but due to differences in process technology, there are differences in the degree of electrolyte infiltration in the battery cells, which makes the cycle performance vary greatly. The C battery cell has better cycle performance, and the 100-week capacity retention rate of the 1C / 3C (charging rate is 1C, and the discharge rate is 3C) cycle performance is 99.61%. The 100-week capacity retention rates of the A and B battery cells are 92.64% and 96.34% respectively, all of which have different degrees of attenuation, such as Figure 1 .
[0031] The ICP test method is now used to quantitatively characterize the element distribution of the positive and negative electrodes of the A / B / C cells to find the root cause (electrolyte infiltration) and improve the electrical performance. By disassembling the A / B / C cells in the empty state after being charged, it can be observed that the negative electrode sheet has obvious poor infiltration at the visual level. Therefore, this embodiment focuses on analyzing the element distribution of the negative electrode sheet, and according to the electrolyte formula of this embodiment, the distribution (infiltration degree) of the three characteristic elements P, S, and B in the cell is mainly examined.
[0032] Analyze the degree of wetting (condition) of A / B / C cells according to the steps:
[0033] S1. Disassemble the battery cell in the empty state after being charged to obtain the positive and negative electrodes. Since it can be observed that the negative electrode has obvious poor electrolyte infiltration at the visual level, the experimental process mainly analyzes the distribution of the three characteristic elements P, S, and B in the negative electrode;
[0034] S2. Divide the negative electrode sheet into 3 (n) equal areas in the length direction (such as Figure 2 The head, middle and tail regions in the middle of each region in the length direction are divided into 3 (m) regions in the width direction of the negative electrode sheet to obtain K first sample regions to be tested, K = 3 × 3 (n × m) = 9, reference Figure 2 In the middle ①~⑨ areas; the length of the first sample area to be tested is L1, the width is W1, and the thickness is H1; L1=50mm, W1=19.6mm, H1=130μm;
[0035] At the same time, the negative electrode sheet is divided into the positive and negative sides with the current collector as the dividing line, and the positive and negative sides are divided into 3 regions in the width direction, and each region is divided into 3 regions in the thickness direction, to obtain Y second sample areas to be tested, Y = 2 × 3 × 3 (2 × x × y) = 9, reference Figure 3 The upper, middle and lower areas of the front and back sides respectively; the length of the second sample area to be tested is L2, the width is W2, and the thickness is H2; L2 = 1563mm, W2 = 19.6mm, H2 = 21.6μm;
[0036] S3. Test the contents of P, S, and B in 9 (K) first sample areas to be tested and 18 (Y) second sample areas to be tested in the negative electrode sheets of A / B / C cells respectively, that is, scrape the powder and take the material from these areas respectively, and then use the ICP test method to test the contents of P, S, and B in these areas; The test results of the contents of P, S, and B in the 9 (K) first sample areas to be tested in the negative electrode sheets are shown in Table 2, and the test results of the contents of P, S, and B in the 18 (Y) second sample areas to be tested in the negative electrode sheets are shown in Table 3; Table 2 Test results of the contents of P, S, and B (elements) in the 9 (K) first sample areas to be tested in the negative electrode sheets of A / B / C cells (sampling in length direction first and width direction second)
[0037]
[0038] Table 3 Test results of P, S, and B (element) contents in 18 (Y) second sample areas in the negative electrode sheets of A / B / C cells (sampling in width direction first and thickness direction second)
[0039]
[0040]
[0041] Analyzing the data in Table 2 and Table 3, it can be seen from Table 2 (sampling in length direction first and width direction second) that the P and S elements in the negative electrode sheets of A and B cells are not much different from those in C cells, but the B element is quite different. And after carefully comparing the P, S, and B content data of each first sample area in the negative electrode sheets of A and B cells in Table 2, it can be found that in the P element distribution matrix and the S element distribution matrix, the P element content ratio and the S element content ratio of any two areas are both less than 2 (with the element content of the area with lower element content as the divisor), which indicates that the P and S elements have a good degree of infiltration in the negative electrode sheets of A and B cells; and it can be further found that in the B element distribution matrix, regarding the B element content ratio of any two areas (with the element content of the area with lower element content as the divisor), it can be calculated that there are more ratios greater than 2, and the largest ratio even reaches 4.62, which indicates that the degree of infiltration of the B element in the negative electrode sheets of A and B cells is insufficient. And after relevant calculations, the average values of B element in A, B, and C cells are 124.7, 121, and 144 respectively. In particular, the content of B element in the middle area of the negative electrode sheet in B cell is about 50% of that in C cell, and A cell is about 42% lower.
[0042] Similar to Table 2, it can be seen from Table 3 (sampling in the width direction first and then in the thickness direction) that the P and S elements of the A and B cells are slightly lower than those of the C cell, but the difference is not large. After careful comparison of the P, S, and B content data of the second sample areas to be tested in the negative electrode sheets of the A and B cells in Table 3, it can be found that the P, S, and B contents of the second sample areas to be tested are respectively positive-1-up, positive-1-middle, positive-1-down, reverse-1-up, reverse-1-middle, reverse-1-down, positive-2-up, positive-2-middle, positive-2-down, reverse-2-up, reverse-2-middle, reverse-2-down, positive-3-up, positive-3-middle, positive-3-down, reverse-3-up, reverse-3-middle, In these areas, the ratio of the P element content and the S element content ratio of any two areas are less than 2 (with the element content of the area with lower element content as the divisor), which shows that the P and S elements have a good degree of infiltration in the negative electrode sheets of A and B battery cells; and it can be further found that in the above-mentioned areas, regarding the ratio of the B element content of any two areas (with the element content of the area with lower element content as the divisor), it can be calculated that there are many ratios greater than 2, and the largest ratio even reaches 4.62, which shows that the degree of infiltration of the B element in the negative electrode sheets of A and B battery cells is insufficient. And after relevant calculations, with regard to the B element, the average B element content of the A battery cell is 94, the average B element content of the B battery cell is 121, and the average B element content of the C battery cell is 212. The B element corresponds to the LiODFB additive, which is mainly used to improve the cycle performance and electrochemical stability. Therefore, it can be concluded that the uneven distribution of the LiODFB additive is the root cause of the deterioration of the cycle performance.
[0043] S4. According to S3, the distribution of the three characteristic elements P, S, and B in the negative electrode sheet of the battery cell (the degree of infiltration) is analyzed from different dimensions. Since the B element has a ratio of more than two areas of the 9 (K) first sample areas to be tested and the 18 (Y) second sample areas to be tested, which is greater than 2 (the element content of the area with lower element content is the divisor), it is judged that the degree of infiltration of the negative electrode sheet with respect to the B element is insufficient. Therefore, according to the above analysis results, the influence of the injection influencing factor on the infiltration is verified by optimizing the injection process parameters and the infiltration is improved. Original process parameters: vacuum degree -87kpa, positive pressure 0.3Mpa, 6 cycles, and standing at room temperature for 24h after injection; Improvement plan 1: vacuum degree -87kpa, positive pressure 0.3Mpa, 10 cycles, and standing at room temperature for 24h after injection; Improvement plan 2: vacuum degree -87kpa, positive pressure 0.3Mpa, 6 cycles, and standing at 45℃ for 24h after injection. The element distribution of the electrode in the empty state after formation of the improvement scheme 1-2 was quantitatively characterized. The element distribution of the positive electrode is not much different in the length and thickness directions of the electrode, and there is a large difference in the element distribution of the negative electrode. The test results of the P, S, and B contents of the 9 (K) first sample areas to be tested in the negative electrode of the improved A / B battery cell (sampling in the length direction first and then in the width direction) and the test results of the P, S, and B contents of the 18 (Y) second sample areas to be tested in the negative electrode of the A / B battery cell are shown in Tables 4 and 5, respectively.
[0044] Table 4 Test results of P, S, and B (element) contents in 9 (K) first sample areas in the negative electrode sheet of the improved A / B battery cell (sampling in length direction first and then in width direction)
[0045]
[0046] Table 5 Test results of P, S, and B (element) contents in 18 (Y) second sample areas in the negative electrode sheet of A / B battery cells (sampling in width direction first and then thickness direction)
[0047]
[0048]
[0049] By analyzing the data in Tables 4 and 5, it can be seen that the three elements P, S, and B in improvement solutions 1 and 2 have increased to a certain extent compared with the C battery cell. As for the B element that affects the cycle performance of the battery cell, in improvement schemes 1 and 2, whether in each first sample area to be tested (sampling in the length direction first and then the width direction in the P, S, and B element distribution matrix respectively), or in each second sample area to be tested (sampling in the width direction first and then the thickness direction in the positive-1-upper, positive-1-middle, positive-1-lower, reverse-1-upper, reverse-1-middle, reverse-1-lower, positive-2-upper, positive-2-middle, positive-2-lower, reverse-2-upper, reverse-2-middle, reverse-2-lower, positive-3-upper, positive-3-middle, positive-3-lower, reverse-3-upper, reverse-3-middle, and reverse-3-lower respectively), the ratio of the P, S, and B element contents of any two areas (with the element content of the area with lower element content as the divisor) is not greater than 2, that is, the wetting performance of the B element in the negative electrode sheet is successfully improved, and the wetting degree of the B element in the negative electrode sheet is further improved. At the same time, it can be seen from Tables 4 and 5 that the average value of the B element of improvement scheme 1 is 225, and the average value of the B element of improvement scheme 2 is 229, both of which are higher than the average value of the B element of C battery cell 212. Figure 4 As shown, it can be seen that in the test of 1C / 5C (charging rate is 1C, discharging rate is 5C) room temperature cycle performance (250 weeks), the improved A and B cells (corresponding to improvement schemes 1 and 2, respectively) are 89.91% for improvement scheme 1, and the capacity retention rate is increased by 1.97%; the improved scheme 2 is 92.42%, and the capacity retention rate is increased by 4.48%. Compared with the capacity retention rate (87.94%) of the 250-week control group (original C cell), it even has a higher capacity retention rate. Therefore, by using the method for analyzing the degree of wetting of the cell provided by the present invention, the degree of wetting of each important component in the electrolyte can be analyzed very accurately from a microscopic perspective (such as the microscopic perspective of the distribution of characteristic elements), so as to accurately find the root cause that affects the electrochemical properties such as the cell cycle performance, and then quickly and effectively make corresponding improvements to the root cause, so as to achieve the purpose of quickly and effectively optimizing the battery cycle performance.
[0050] In addition, the application of the present invention is not limited to characterizing the three elements P, S, and B contained in the electrolyte. For example, the distribution of Si elements in the widely used silicon-based negative electrode at this stage can also be characterized by this method. The capacity of the Si negative electrode is high and the expansion coefficient is high. Whether the dispersion of the Si element is uniform seriously affects the electrical properties of the negative electrode. In addition, some impurity metal elements can also be tested, such as Al, As, Bi, Ca, Cd, Co, Cr, Cu, Fe, Ga, Ge, In, Ir, K, La, Li, Mg, Mn, Mo, Na, Nb, Ni, Pb, Sb, Sn, Sr, Ta, Ti, V, W, Y, Zn, Zr, etc.
[0051] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A method for analyzing the degree of wetting of a battery cell, characterized in that: The steps include: S1. Disassemble the battery cell after being transformed into an empty state to obtain an electrode; the electrode contains an electrolyte, and the electrolyte contains characteristic elements; the electrode comprises at least one of a positive electrode and a negative electrode; S2. The pole piece is equally divided into n regions in the length direction, and the center position in the length direction of each region is equally divided into m regions in the width direction of the pole piece to obtain K first sample regions to be tested, K = n × m; the length of the first sample region to be tested is L1, the width is W1, and the thickness is H1; At the same time, the electrode sheet is divided into a front side and a back side with the current collector as a dividing line, and the front side and the back side are divided into x regions in the width direction, and each region is divided into y regions in the thickness direction, to obtain Y second sample regions to be tested, Y=2×x×y; the second sample region to be tested has a length of L2, a width of W2, and a thickness of H2; S3. Test the content of the characteristic elements in the K first sample areas and the Y second sample areas in the electrode; the characteristic elements include at least one of P, S, B, F, N, Si, Al, As, Bi, Ca, Cd, Co, Cr, Cu, Fe, Ga, Ge, In, Ir, K, La, Li, Mg, Mn, Mo, Na, Nb, Ni, Pb, Sb, Sn, Sr, Ta, Ti, V, W, Y, Zn, and Zr; S4. When, in the first sample area to be tested of the electrode, the ratio of the characteristic element content between any two areas is greater than 2, wherein the characteristic element content of the area with lower characteristic element content is used as the divisor; and / or, when, in the second sample area to be tested of the electrode, the ratio of the characteristic element content between any two areas is greater than 2, wherein the characteristic element content of the area with lower characteristic element content is used as the divisor; it is judged that the degree of wetting of the electrode is insufficient.
2. The method for analyzing the degree of wettability of a battery cell according to claim 1, characterized in that: In S2, in the K first sample areas to be tested, when the electrode is a positive electrode, L1≥50mm, W1≥19.6mm, H1≥106μm; when the electrode is a negative electrode, L1≥50mm, W1≥19.6mm, H1≥130μm; In the Y second sample areas to be tested, when the electrode is the positive electrode, L2≥1492mm, W2≥19.1mm, H2≥17.6μm; when the electrode is the negative electrode, L2≥1563mm, W2≥19.6mm, H2≥21.6μm.
3. The method for analyzing the degree of wetting of a battery cell as claimed in claim 2, characterized in that: In S2, in the K first sample areas to be tested, when the electrode is a positive electrode, L1=50mm, W1=19.6mm, H1=106μm; when the electrode is a negative electrode, L1=50mm, W1=19.6mm, H1=130μm; In the Y second sample areas to be tested, when the electrode is the positive electrode, L2=1492mm, W2=19.1mm, H2=17.6μm; when the electrode is the negative electrode, L2=1563mm, W2=19.6mm, H2=21.6μm.
4. The method for analyzing the degree of wetting of a battery cell as claimed in claim 1, characterized in that: In S2, K≥9; Y≥18.
5. The method for analyzing the degree of wetting of a battery cell as claimed in claim 4, characterized in that: In S2, K=9; Y=18.
6. The method for analyzing the degree of wetting of a battery cell as claimed in claim 1, characterized in that: In S2, the characteristic element includes at least one of P, S, and B.
7. The method for analyzing the degree of wettability of a battery cell according to claim 1, characterized in that: In S2, the characteristic element content in the pole piece is tested using an inductively coupled plasma spectrometer.
8. The method for analyzing the degree of wetting of a battery cell as claimed in claim 1, characterized in that: The electrolyte comprises the following components: lithium salt, organic solvent, film-forming additive, and functional additive; the mass ratio of the lithium salt: the organic solvent: the film-forming additive: the functional additive is 12-18:74-85:2-5:1-4; The lithium salt includes lithium hexafluorophosphate; The organic solvent comprises at least one of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate; The film-forming additive includes at least one of fluoroethylene carbonate and vinylene carbonate; The functional additive includes at least one of lithium bis(fluorosulfonyl)imide, lithium difluorobis(oxalatophosphate), lithium difluorophosphate, lithium bis(oxalatoborate), 1,3-propanesultone, and vinyl sulfate.
9. The method for analyzing the degree of wetting of a battery cell as claimed in claim 1, characterized in that: The positive electrode sheet includes a positive electrode material, a first conductive agent, and a first binder; the mass ratio of the positive electrode material, the first conductive agent, and the first binder is 95-99: 1-3.5: 0.5-1.5; The positive electrode material includes at least one of a lithium iron phosphate positive electrode material, a ternary nickel cobalt lithium manganese oxide positive electrode material, and a lithium iron manganese phosphate positive electrode material; The first conductive agent includes at least one of conductive carbon black and carbon nanotubes; the first binder includes at least one of polyvinylidene fluoride; The negative electrode sheet comprises a negative electrode material, a second conductive agent, and a second binder; the mass ratio of the negative electrode material, the second conductive agent, and the second binder is 95-99: 0.3-2: 1-3.5; The negative electrode material includes at least one of natural graphite, artificial graphite, and silicon-carbon negative electrode; The second conductive agent includes conductive carbon black; the second binder includes at least one of carboxymethyl cellulose and styrene-butadiene rubber.
10. The method for analyzing the degree of wettability of a battery cell according to claim 1, characterized in that: The battery cell comprises a cylindrical battery cell.
Citation Information
Patent Citations
Lithium ion battery electrolyte infiltration judgment method
CN113866155A
Method for analyzing distribution state of electrolyte in battery cell and application of method
CN113945676A
Method for testing infiltration degree of roll core
CN114354449A
Method for evaluating wettability of lithium ion battery pole piece
CN115326961A
Method and device for testing infiltration degree of battery electrolyte
CN117388122A
Cited By
Method for measuring infiltration degree of electrolyte of battery cell
CN121977974A
Method for measuring degree of electrolyte impregnation of an electric cell
CN121977974B